1982
DOI: 10.1083/jcb.92.2.462
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the components of extracellular matrix and in growth properties of cultured aortic smooth muscle cells upon ascorbate feeding.

Abstract: Culture conditions can modify the composition of the extracellular matrix of cultured calf aorta smooth muscle cells. In the absence of ascorbate the major components of the matrix are microfibrillar proteins ; deposition of collagen occurs upon ascorbate supplementation and, with increased time of exposure of cells to ascorbate, collagen becomes the dominant protein of the extracellular matrix (>80%) . Collagen accumulation follows a sigmoidal time-course, suggesting that it is a cooperative phenomenon . Cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 32 publications
(31 reference statements)
3
27
0
Order By: Relevance
“…AA plays a major role in the deposition of matrix collagen through its function as a co-factor for proline hydroxylase [8]. Similarly, synthesis of matrix PG and matrix glycoproteins, such as fibronectin and laminin, is enhanced when the medium is supplemented with AA [10, 11, 12, 24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AA plays a major role in the deposition of matrix collagen through its function as a co-factor for proline hydroxylase [8]. Similarly, synthesis of matrix PG and matrix glycoproteins, such as fibronectin and laminin, is enhanced when the medium is supplemented with AA [10, 11, 12, 24].…”
Section: Discussionmentioning
confidence: 99%
“…AA is an important anti-oxidant, and this is particularly relevant in this context, as diabetes has been shown to be a state of increased oxidative stress which can affect endothelial cell function [6, 7]. Tissue culture experiments, involving a number of human and animal cell types, have also shown that deposition of matrix collagen, glycoproteins, and proteoglycans (PG) is enhanced by AA [8, 9, 10, 11, 12]. In addition, we have previously shown that AA affects PG of rat mesangial matrix qualitatively, by increasing its degree of sulphation [13].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that FBM and SMCM composition from cells in culture may differ from their connective tissue matrix in vivo, e.g., in collagen composition. Preliminary data have shown that the addition of vitamin C to culture medium influences synthesis and post-translational modification of collagen 19 and results in aggregate formation on FBM and SMCM. 20 Optimal conditions approximating the in vivo situation are difficult to determine, which implies that direct extrapolation to the in vivo situation is not allowed.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary for VSMC collagen synthesis, since without it (Schwartz et al, 1982), or in the presence of the non-functional ascorbate analog ethyl-3,4-dihydroxybenzoate (Sasaki et al, 1987), VSMCs form little collagen. In addition to enhancing post-translational collagen modification in VSMCs, ascorbate also increases procollagen synthesis by a pre-translational mechanism (Barone et al, 1985;Davidson et al, 1997).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Effect of Vitamin C: References Direct oxidation of LDL Prevents (Frei et al, 1989;Niki et al, 1995) Recycles α-tocopherol (Frei, 1991) Endothelial cell dysfunction Nitric oxide generation Enhances (Heller et al, 1999;Heller et al, 2001; (Schwartz et al, 1982) Monocyte/macrophages LDL uptake and modification Controversial (Stait & Leake, 1994) Inflammatory markers Inhibits (May et al, 2005b) Nitric oxide release Inhibits (Mizutani et al, 1998) …”
mentioning
confidence: 99%